KARAKTERISASI SENSOR PHOTODIODA, DS18B20, DAN KONDUKTIVITAS PADA RANCANG BANGUN SISTEM DETEKSI KEKERUHAN DAN JUMLAH ZAT PADAT TERLARUT DALAM AIR - Zulfiah Ayu Kurnia Sari; Handjoko Permana; Widyaningrum Indrasari (Program Studi Fisika Universitas Negeri Jakarta, 2017)
Abstract Drinking water worth consumption are those that should be odorless, tasteless, clean, the temperatures preferably below air temperature, and low amounts of dissolved solids. On this turbidity and total dissolved solid water system is required some sensor devices. The accuracy of the sensor is an important thing to support the effectiveness of the system. In this research, the calibration of ds18b20 sensor as temperature detector, photodiode sensor as turbidity detector, and conductivity sensor as a detector of dissolved solid (TDS) in water and using Arduino as a microcontroller. The characterization is done by comparing the sensor output with laboratory test equipment. The result of characterization means that each measurement sensor has a variation error that is photodiode sensor with relative error 3.13%, sensor ds18b20 1.77%, and conductivity sensor 2.42%. Keywords: temperature, turbidity, TDS, Arduino.